Penerapan Metode Concept Sentence Untuk Meningkatkan Hasil Belajar IPS - Nursanti, Ermina (JURNAL SINEKTIK, 2024)
The purposes of this research are describing the application of the Concept Sentence Method on the Social Science about the Interaction between Countries in Asia and other Countries in Class IX I of 1 Rembang Junior High School, First Semester 2023/2024 Academic Year and analyzing the enhancement of learning outcomes. The type of this research is Class Action Research (CAR). The place of this research is in class IX I of 1 Rembang Junior High School. The time of this research is middle of August until early of September. The subjects of this research are 30 students; consist of 16 boys and 14 girls. The techniques of collecting data are test with multiple choices as the tool and non test with sheet of observation and camera application as the tools. The technique of analyzing data of this research is comparative description. The model of this research is Cycle Model. The results of this research are the application of the Concept Sentence Method in individually with synchronized the concepts to the material coverage and the learning outcomes enhanced gradually and continuously. Keywords: Concept Sentence Method, Learning Outcomes, Social Science.